Time-varying characteristics of bridges under the passage of vehicles using synchroextracting transform. (June 2020) - Li, Jiantao; Zhu, Xinqun; Law, Siu-seong; Samali, Bijan
Highlights: A new method to extract the time-varying characteristics of bridges under the passage of vehicles. Vehicle and bridge instantaneous frequencies are extracted by synchroextracting transform. The effects of vehicle parameters, road surface roughness and measurement noise are numerically investigated. Laboratory and field testing are conducted to further validate the proposed approach. Abstract: The vehicle and bridge responses in a vehicle-bridge interaction (VBI) system have been widely studied with some aiming at the bridge health monitoring. The extraction of bridge modal frequencies from bridge or vehicle responses was mostly conducted with the assumption of an invariant vehicle and bridge system and/or the responses are stationary during the interaction. This assumption may be appropriate when the vehicle mass is negligible compared with the bridge mass. The vehicle and bridge frequencies are time-varying in practice during the VBI process and these time-varying characteristics are potential indicators for bridge condition assessment. This paper presents a new method to extract the time-varying characteristics of the bridge under the passage of vehicles. A time-frequency (TF) analysis method, the synchroextracting transform, is adopted for the purpose. It is a post-processing procedure with short-time Fourier transform to improve the TF resolution on the time-varying features of the signal. The instantaneous frequency of mono-components related to the vehicle and bridge frequencies can then be extracted from the time-frequency representation of the responses. Numerical investigation is conducted to study the effect of measurement noise, vehicle properties and road surface roughness on the identified results. Laboratory and field tests are also conducted to validate the proposed approach. Results show that the time-varying characteristics are good indicators for bridge condition assessment.